Time trends in incidence of diabetes mellitus in Austrian children and adolescents <15 years (1989‐2017). Issue 5 (31st May 2020) - Rami‐Merhar, Birgit; Hofer, Sabine E.; Fröhlich‐Reiterer, Elke; Waldhoer, Thomas; Fritsch, Maria
Abstract: Objective: To analyze the time trends of nationwide diabetes incidence <15 years of age from 1989 until 2017 in Austria. Methods: The Austrian Diabetes Incidence Study Group registers all newly diagnosed patients with diabetes mellitus <15 years of age in a prospective population‐based study. The diabetes type was classified on the basis of clinical and laboratory findings according to American Diabetes Association criteria. Time trends were estimated by Joinpoint analysis. Results: 1311 patients were diagnosed with type 1 diabetes (T1D) between 1989 and 1999 and 4624 patients with any type of diabetes (1999‐2017). T1D accounted for the majority of cases (94.2%), 1.8% were classified as type 2 (T2D) and 4.0% as other specific types of diabetes (1999‐2017). In the total cohort (age 0 to <15 years), a constant increase until 2012 (annual percent change [APC] 4.5, 95% confidence interval [CI]: 3.94, 5.06) was observed, followed by a leveling off with a corresponding drop (APC 0.28, 95%CI: −3.94, 4.69). This observation was mainly driven by the dynamic in the youngest age group (0‐4 years) with a steep increase until 2007 (APC 7.1, 95%CI: 5.05, 9.19) and a decrease from 2007 to 2017 (APC −0.86, 95%CI: 4.41, 2.82). No significant increase of T2D <15 years was detected. Over the observed time period (APC = 3.7, 95%CI: −0.30, 7.78). Conclusions: The incidence of T1D is declining in young children aged 0 to 4 years, but is still rising in children 5 to 14 years in Austria. Incidence of T2D did not increase significantly and other specific types of diabetes occur twice as often compared to T2D.